2008
DOI: 10.14198/jopha.2008.2.2.04
|View full text |Cite
|
Sign up to set email alerts
|

Domestic applications for social robots: an online survey on the influence of appearance and capabilities

Abstract: Abstract-Can you imagine a useful task you would like a social robot to perform for you? This paper presents an internet survey where participants were asked this question to identify applications for social robots. The applications mentioned by the participants are based on the appearance of four social robots (AIBO, iCat, BIRON, and BARTHOC) and the information they received about their basic capabilities. It was found that AIBO and iCat seem to be suitable for domestic applications whereas suggested applica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 33 publications
0
35
0
1
Order By: Relevance
“…When considering the task domain, many researchers suggested the consistency between a robot's appearance and its task [23,25,31]. In Goetz et al's study, they used a 2-D robotic head with three levels of human-likeness (i.e.…”
Section: Compatibility Between Robot Appearance and Taskmentioning
confidence: 99%
See 1 more Smart Citation
“…When considering the task domain, many researchers suggested the consistency between a robot's appearance and its task [23,25,31]. In Goetz et al's study, they used a 2-D robotic head with three levels of human-likeness (i.e.…”
Section: Compatibility Between Robot Appearance and Taskmentioning
confidence: 99%
“…In Lohse et al's study, the robots were classified as humanoid, zoomorphic and functional robots. Participants were presented short movies with descriptions of robots, and were asked about appropriate tasks for these robots [31]. In both studies, some appropriated applications were identified for each type of robots.…”
Section: Compatibility Between Robot Appearance and Taskmentioning
confidence: 99%
“…Much has also been written about the role of the uncanny valley in HRI and the problems with robots that fall through the cracks of human-like behaviour [18]. The third paper in this special issue by Lohse et al [19] makes a contribution to this debate by comparing human reactions to a number of different robots -including a humanoid device.…”
Section: This Issue Contentmentioning
confidence: 99%
“…The occupational background of a robot could be shown to help participants ground a conversation, even if not all users always followed the social norms of human-human communication [5]. The responses differ and also the expectations vary and tend towards a more social direction the more anthropomorphized the system design is [6]. Much research on feedback in HRI is dedicated to investigating single modalities or communication-based verbal scenarios in combination with one additional modality [7], [8], [9].…”
Section: Introductionmentioning
confidence: 99%